Nanoscale chemical speciation of β-amyloid/iron aggregates using soft X-ray spectromicroscopy. Issue 6 (18th January 2021) - Everett, James; Brooks, Jake; Collingwood, Joanna F.; Telling, Neil D.
Abstract : Nanoscale resolution X-ray spectromicroscopy shows the co-incubation of β-amyloid (Aβ) and iron(iii ) to result in aggregate structures displaying nanoscale heterogeneity in Aβ and iron chemistry, including the formation of potentially cytotoxic Fe 0 . Abstract : Iron (Fe) is an essential trace element required for healthy brain function. Yet, disrupted iron neurochemistry, and the associated formation of aberrantly aggregated protein lesions has been implicated in the development of multiple degenerative brain disorders including Alzheimer's disease (AD). Here, nanoscale resolution soft X-ray spectromicroscopy is used to examine the interaction of β-amyloid (Aβ), a peptide fundamentally implicated in the development of Alzheimer's, and ferric (Fe 3+ ) iron. Crucially, by probing the carbon K (280–320 eV) and iron L2, 3 (700–740 eV) edges, both the organic and inorganic (iron) sample chemistry was established. The co-aggregation of Aβ and iron is known to influence iron chemistry, resulting in the chemical reduction of Fe 3+ into reactive and potentially toxic ferrous (Fe 2+ ) and zero-oxidation (Fe 0 ) states. Here, nanoscale ( i.e. sub-micron) variations in both iron oxidation state and the organic composition of Aβ were observed, replicating in vitro the diverse iron chemistry documented in amyloid plaques from human brain, with the chemical state of iron linked to the conformation state of Aβ. Furthermore, aggregates were formed that were morphologically and chemically distinct dependent on the treatment of Aβ prior to the addition of ferric iron. These findings support the hypothesis that Aβ is responsible for altering iron neurochemistry, and that this altered chemistry is a factor in neurodegenerative processes documented in AD. The methods applied here, combining nanoscale-resolution imaging and high chemical sensitivity, enabled discovery of the nanoscale heterogeneity in the iron and carbon chemistry of in vitro aggregates, and these approaches have scope for wider application in metallomics.